2014
DOI: 10.1186/1756-0500-7-65
|View full text |Cite
|
Sign up to set email alerts
|

Chinese culture permeation in the treatment of Parkinson disease: a cross-sectional study in four regions of China

Abstract: BackgroundLittle is known about the clinical features and treatment of Chinese patients with Parkinson disease (PD).MethodsA large cross-sectional survey of clinical features, medication use, and motor complications was conducted in 901 consecutive PD patients, from 42 randomly selected university-affiliated hospitals in four urban economic regions of China, between December 2006 and May 2007.ResultsThe 901 PD patients had age range 30 to 88, and median disease duration 50 months. Most (737, 81.8%) used L-dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…According to a nationwide survey in China, the median LEDD was 450 mg for PD patients with a median disease duration of 50 months. [ 23 ] However, whether the actual need for medications is different between Chinese patients and those in other countries remains unknown. The lower voltage in our patients is explained as follows: (1) Some patients have a low threshold for side effects and therefore cannot bear a higher voltage; (2) The smaller body size might play a role in determining the lower effective voltages in Chinese patients; and (3) A relatively low voltage exerts a therapeutic effect as long as the electrodes are placed in the STN precisely.…”
Section: Discussionmentioning
confidence: 99%
“…According to a nationwide survey in China, the median LEDD was 450 mg for PD patients with a median disease duration of 50 months. [ 23 ] However, whether the actual need for medications is different between Chinese patients and those in other countries remains unknown. The lower voltage in our patients is explained as follows: (1) Some patients have a low threshold for side effects and therefore cannot bear a higher voltage; (2) The smaller body size might play a role in determining the lower effective voltages in Chinese patients; and (3) A relatively low voltage exerts a therapeutic effect as long as the electrodes are placed in the STN precisely.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a delay in the use of levodopa was recommended, because dyskinesia could be induced by early use of levodopa. However, the principle of early used low dose had been proposed for many years in China and several studies provided evidence that early use of a low dose (≤400 mg/d) of levodopa did not increase the incidence of dyskinesia [ 10 , 11 , 17 ], which was supported by the results of Olanow’s study [ 12 ]. Immediate-release levodopa/benserazide or levodopa/carbidopa shows fast acting effects, while controlled-release levodopa/benserazide or levodopa/carbidopa produces slow acting effects with low bioavailability.…”
Section: Contentsmentioning
confidence: 97%
“…A large clinical survey of 901 patients from 4 different regions in China identified that patients take lower doses of dopaminergic drugs, and subsequently have less drug-induced complications compared to Western populations [65]. The development of dyskinesia has been reported to be significantly lower compared to Western countries [66].…”
Section: Discussionmentioning
confidence: 99%